ESCRT or endosomes?: Tales of the separation of two daughter cells - Schiel, John A (Landes Bioscience, 2011)
The final abscission event of cytokinesis is necessary for daughter cells to part ways from one another. Failure to properly divide has been indicated as a potential cancer initiating event due to an increase in cellular aneuploidy. However, the exact mechanisms of abscission have remained obscured by our inability to properly discern the spatiotemporal regulation of the various proteins and organelles required for cytokinesis. Three recent publications have taken slightly varied high resolution imaging approaches to visualize cytokinesis and abscission. As a result of this work, two differing, but not necessarily mutually exclusive, models have emerged. One model is ESCRT-dependent and the other, recycling endosome-dependent, each describing the steps leading up to the final abscission event. Presently these models describe late cytokinesis events leading to abscission in greater detail than previously known.